ANALYSIS OF PATIENT SATISFACTION WITH THE QUALITY OF OUTPATIENT SERVICES IN THE INTERNAL MEDICINE POLYCLINIC OF THE PRABUMULIH GENERAL HOSPITAL - Dina Riana; Akhmad Dwi Priyatno; Chairil Zaman; Sutriana Sabrina N; Indra Martiandra (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Public satisfaction is influenced by healthcare services because it is one of the factors contributing to improving the quality of healthcare services. The results of the public satisfaction survey have fluctuated over the past three years, from 2022 to 2024. In 2022, the SKM score was 81.25 in the first semester and 80.70 in the second semester, in 2023, 81.70 in the first semester and 81.35 in the second semester, and in 2024, 82.425 in the first semester and 85.2 in the second semester. The research method used a cross-sectional approach. The population consisted of outpatients receiving treatment at the internal medicine polyclinic at Prabumulih General Hospital. A purposive sampling technique was used to obtain 88 respondents. The study found no correlation between age, gender, and assurance on patient satisfaction. However, the variables that were correlated with patient satisfaction were education (p-value = 0.021), tangibles (p-value = 0.035), reliability (p-value = 0.008), responsiveness (p-value = 0.001), and empathy (p-value = 0.001). The final multivariate analysis revealed that the dominant variable influencing satisfaction was responsiveness, with a p-value = 0.009 and an Exp(B) value of 22.654. Conclusion: There is a significant correlation between education, tangibles, reliability, responsiveness, and empathy on outpatient satisfaction at Prabumulih City Hospital. Responsiveness was the dominant variable